Tumor-stroma cross talk and platelets: Curse of cancers - Ashok Vikey (Annals of Molecular and Genetic Medicine - Peertechz Publications, 2020)
Platelets are essential part of our vascular system, named as thrombocytes and their main role is to stop bleeding; by clumping and aggregating at damaged vascular location. Embryonically the platelets originate in bone marrow from megakaryocytes. These are smallest structures among blood cells, with average dimensions less than 4 microns in size, biconvex or straight ends and normally are colorless without nucleus [1].